A Field Trial Comparing 20 Different Rootzone Mixes of Various Organic and Inorganic Amendments. Issue 1 (1st January 2013) - Dinelli, Dan
Abstract : A short game practice facility was constructed at North Shore Country Club, Glenview Illinois in the summer of 1997. In addition to it being a functional practice area, the design included various research objectives including field‐testing several rootzone amendments in the 7, 200 square feet putting green. All rootzones were constructed with the same sand, meeting USGA specifications in particle size and distribution and built to a USGA profile standard. 20 different rootzone mixes were used in cells measuring 14' × 15' and 12" deep. A permanent 80‐mil high‐density polyethylene barrier extending from the top of the pea gravel bed to the surface divided the cells. All plots were seeded with a 50/50 blend of L‐93 and SR‐1119 at 2 lbs/1, 000 ft 2 . A seed blanket was used to assist grow‐in and protect from any potential erosion until seedling establishment. All plots were managed equally and topdressed with straight sand as the turf matured. Rootzone cells consisted of: Straight Sand; 85/15 Sphagnum Peat; 90/10 Dakota Peat; 90/10 Dakota Peat plus Chip Humate (250#); 90/10 Dakota Peat plus 22.5% Profile (porous ceramic); 90/10 Dakota Peat plus 15% (v/v) Profile and 350 pounds ZeoPro (zeoponic zeolite); 90/10 Dakota Peat plus 10% (v/v) Zeopro; 90/10 Dakota Peat plus 10% Axis (calcined diatomaceous earth); 90/10 Dakota Peat plus 10% Axis and 350 pounds Zeopro; 90/10 Dakota Peat plus 100 pounds OptiMil (granular Sea Plant Meal and Milorganite with sunflower seed hull ash, total N‐P‐K of 3‐1‐4); 90/10 Dakota Peat plus 100 pounds OptiMil and Emerald Isle Microbial Trichoderma harzianum and endomycorrhizal fungi; 90/10 Dakota Peat plus 60 pounds SAND_AID (granular Sea Plant Meal, 1‐0‐1); 90/10 Dakota Peat plus 60 pounds SAND‐AID and Emerald Isle Microbial Trichoderma harzianum and endomycorrhizal fungi; 90/10 Dakota Peat plus 300 pounds Paramagnetic basalt rock, 40 pounds Hard Rock Phosphate and 40 pounds Greensand; 90/10 Yardwaste Compost; 90/10 Biosolids; 90/5/5 yardwaste/biosolids; Sand mixed with 10 pounds Hydrozone (water absorbing polyacrylamide copolymer); Sand mixed with 5 pounds Hydrozone and earthworm castings; and 90/10 local peat. The results will be presented and discussed.